OPERATIONAL MANAGEMENT STRATEGY AT MB BAKERY AND COFFEE IN BESUSU TENGAH PALU CITY - Azmi, Akhroja Nur; Miru, Sulaeman; Syamsuddin (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2025)
This study explores the strategic operational management decisions implemented by MB Bakery & Coffee and evaluates its competitive position within Palu City's coffee shop industry using Porter’s Five Forces analysis. A descriptive qualitative method was employed, with data collected through in-depth interviews conducted in Besusu Tengah Urban Village, East Palu District. The analysis focused on ten strategic decisions in operational management, revealing how MB Bakery & Coffee has adapted to the dynamic and competitive landscape.The Porter’s Five Forces framework identified several key findings. First, the emergence of new coffee shops in Palu presents a significant competitive threat, requiring MB Bakery & Coffee to strengthen its value proposition. Second, customer purchasing power remains stable, primarily supported by loyal, long-standing patrons. However, the influx of new cafés and shifting customer preferences present challenges in attracting new clientele. Third, the threat of substitute products is currently minimal, though continuous innovation is essential to sustain market relevance. Fourth, supplier power is notably high, as MB Bakery & Coffee maintains strict quality standards for food ingredients and coffee beans, reinforcing its commitment to product excellence. Lastly, competition intensity is strong, with 67 coffee shops recorded in Palu City as of 2023. MB Bakery & Coffee faces direct rivalry from two businesses with similar concepts, highlighting the need for ongoing strategic refinement.The study concludes that while MB Bakery & Coffee has effectively executed several operational strategies, maintaining a competitive edge in Palu’s saturated market requires continual innovation, quality control, and customer engagement